Can Open Pedagogy Encourage Care? Student Perspectives - Maultsaid, Deirdre; Harrison, Michelle (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
As a response to the increasing commercialization of postsecondary education, educators argue for a practice of care in education. Open pedagogy (OP) seems like an ideal practice where care, trust, and inclusion can be realized. OP is characterized as a democratic and collaborative pedagogical practice, in which students and teachers work to co-create learning and knowledge using openly licensed materials, open platforms, and other open processes. The purposes of this study were, first, to reveal ways students in postsecondary institutions perceive care and, second, to determine how students suggest OP can be used to create an open/caring learning process. A task-oriented focus group method engaged students from four teaching-focused institutions. The students created open cases on social issues for class discussion and reflected on care and OP processes in postsecondary settings. Using four elements of the ethics of care—attentiveness, responsibility, competence, and trustworthiness—as conceptual categories, the study examined students’ experience of care and care in OP using affective coding and thematic analysis. The results showed that through OP, with teacher support and explicitly designed practices of care, students can assert their agency, have quintessential roles in creating and participating in highly relevant curriculum and importantly, care about others, and be cared for. OP is a process able to involve a diverse population of students and embody care as an all-encompassing practice.